Compiling and analyzing a tagged learner corpus: a corpus-based study of adjective uses - Castillo Rodríguez, Cristina; Díaz Lage, José María; Rubio Martínez, Beatriz (Círculo de Lingüística Aplicada a la Comunicación, 2020)
A learner corpus (LC) is widely known as a rich source of information regarding the use of expressions and the errors made by students in their productions. In fact, we, as teachers, can profit from the compilation of their tasks so as to analyze in detail their way of writing. However, the mere compilation of texts does not guarantee a successful exploitation, as more steps than saving texts must be involved in the whole process. Therefore, it seems essential to follow a protocolized methodology of compilation. In this paper we propose five phases for compiling a LC containing texts from the spontaneous written productions from undergraduate and postgraduate students. The outcomes thrown with the LC exploitation will reveal the errors in students’ productions regarding the use of plural, comparative and superlative in adjectives and also other fails detected in the tagging phase, most of which are due to students’ misuses.
Keywords: English as a foreign language; applied linguistics; learner corpora; error analysis